How does circular economy respond to greenhouse gas emissions reduction: An analysis of Chinese plastic recycling industries. (August 2018) - Liu, Zhe; Adams, Michelle; Cote, Raymond P.; Chen, Qinghua; Wu, Rui; Wen, Zongguo; Liu, Weili; Dong, Liang
Abstract: With the necessity of greenhouse gas (GHG) emissions reduction as a backdrop, the circular economy (CE) is increasingly being considered an effective response to this issue. Currently, China is facing a considerable challenge as it tries to respond to Paris Agreement targets; however, in many respects China is ahead of other nations as it relates to the implementation of such innovative strategies such as the circular economy policies. For over ten years, China has been investigating how the circular economy policies could be used to respond to GHG emission issue. In particular, the effects of such economic development pattern needs to be identified as well as the specific influence on GHG emissions reduction. This study presents an analysis of the Chinese plastic recycling industries (CPRI) through this lens. Plastics were specifically targeted, as such waste generation represents one of the highest fractions of global waste by mass, as well as the increasing public concerns of the environmental impacts of post-consumer plastics waste. Integrating the concepts of circular economy in this industry could be deemed an effective strategy, one which not only reduces post-consumer waste pollution, but also mitigates GHG emissions. This study analyzes the trajectories, features and driving forces of GHG emissions reduction achieved by the CPRI in the past ten years. The results show that the contribution of the CPRI to [specifically] CO2 emissions reduction increased from 7.67 million tons (MT) in 2007 to 14.57 MT in 2016; the scale factor and structure factor had significant impacts on GHG emissions reduction changes. A scenario analysis is presented based on projected impacts of various relevant national strategies. Finally, the policy implications of the CPRI's further GHG reduction measures are proposed. Graphical abstract: fx1 Highlights: Urgent issue of GHG emissions reduction and its connection with circular economy are introduced. The trajectories, features and driving forces of GHG reduction achieved by the CPRI in the past ten years are analyzed. The scenario analysis is also conducted for the following 15 years according to the relevant national strategies. Policy implications for responding GHG emissions reduction of CPRI are proposed.